Preventing Breast Cancer-Related Lymphedema in High-Risk Patients: The Impact of a Structured Surveillance Protocol Using Bioimpedance Spectroscopy - Whitworth, Pat W.; Shah, Chirag; Vicini, Frank; Cooper, Andrea (Frontiers in Oncology, 2018)
Purpose: We evaluated the impact of structured surveillance using bioimpedance spectroscopy (BIS) to reduce the rate of chronic breast cancer related lymphedema (BCRL) in high-risk patients undergoing axillary lymph node dissection (ALND). Methods: From April 2010 through November 2016, 93 patients who underwent ALND were prospectively monitored with BIS using L-Dex. Intervention for an L-Dex increase of > 10 consisted of applying an over the counter (OTC) sleeve followed by re-evaluation after 4 weeks. The utilization of complete decongestive physiotherapy (CDP) represented a surrogate for chronic BCRL. Results: Median follow-up was 24 months. 55% of patients received taxane-based chemotherapy, 24% received some form of regional nodal irradiation (RNI- includes additional fields or high tangents) and 74% had an elevated body mass index (BMI) with the median number of nodes removed being 19. Overall, 75% of these patients had at least one additional high-risk feature (taxane chemotherapy, RNI, elevated BMI), 48% had at least two, and 6% had all. Thirty-three patients (35.4%) developed an elevated L-Dex score with only 10 (10.8%) requiring CDP (30.3% of those undergoing treatment with sleeve). At last follow-up, only three patients (3%) had unresolved BCRL. Conclusions: The results of this analysis support previous data regarding prospective BCRL surveillance and early intervention using BIS. With this approach, only 3% of patients have chronic BCRL.